Smart Cupboards at Community Learning Activity Center Wiyata Utama - Imelda U. V. Simanjuntak; Lukman Medriavin Silalahi; Ketty Siti Salamah; Fina Supegina; Rachmat Muwardi (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
To address security issues at PKBM Wiyata Utama, the Mercu Buana University (UMB) community service team proposes replacing conventional lockers with smart lockers that use electromagnetic automatic lock technology and special codes. These smart lockers are connected to a microprocessor that controls access to the cupboard doors, allowing only authorized users to open them. The proposed solution aims to provide a safer and more reliable way to address locker security problems and will be shared through mass media and community service journals to raise awareness about the benefits of adopting Smart Cupboards. This initiative has the potential to improve the value system, promote the application of science and technology, and contribute to increasing security and tranquility while educating about positive values for collective progress.